PENGARUH CUSTOMER RELATIONSHIP MARKETING, DAN NILAI NASABAH TERHADAP KEPUASAN DAN LOYALITAS NASABAH BRI CABANG KANDIS DI KABUPATEN SIAK - Ristian Prasetyo; Jushermi Jushermi; Henni Novia Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at BRI Cabang Kandis Kabupaten Siak. The purpose of this study is to determine the influence of Customer Relationship Marketing, and Customer Value to Customer Satisfaction and Loyalty at BRI Cabang Kandis Kabupaten Siak. The number of samples in this study is 100 customers at BRI Cabang Kandis Kabupaten Siak. The determination of the sample by using accidental sampling method is the sampling technique that is done based on the needs. Data analysis conducted in this research using Path Analysis Model (Path Analysis). The results of this study obtained the following conclusions: 1) Customer Relationship Marketing has a positive and significant impact on Customer Satisfaction, 2) Customer Value has a positive and significant impact on Customer Satisfaction, 3) Customer Relationship Marketing has a positive and significant impact on Customer Loyalty. 4) Customer Value has a positive and significant effect on Customer Loyalty. 5) Customer Satisfaction has positive and significant effect on Customer Loyalty, 6) Customer Relationship Marketing has positive and significant impact on Loyalty through Customer Satisfaction. 7) Customer Value has a positive and significant effect on Loyalty through Customer Satisfaction at BRI Cabang Kandis Kabupaten Siak.Keywords : Customer Relationship Marketing, Customer Value, Customer Satisfaction and Customer Loyalty